Shear and tensile bond strengths of autoclaved aerated concrete (AAC) masonry with different mortar mixtures and thicknesses - Tandon, Raghav; Maharjan, Sanjeev; Gautam, Suraj (Journal of Engineering Issues and Solutions, 2021)
Autoclaved aerated concrete (AAC) blocks are commonly used for masonry walls. In order to understand the strength of AAC masonry, it is essential to assess the tensile and shear bond strengths of the AAC block-mortar interface for various mortar combinations. This research investigates the bond strength of AAC block mortar interface made up of a) polymer modified mortar (PMM) and b) ordinary cement sand mortar of 1:4 or 1:6 ratio with thickness of 10mm, 15mm or 20mm. A thin cement slurry coating was applied on the block surface before placing the cement sand mortar in the masonry. For all types of interface, shear bond strength of masonry was studied using a triplet test, while the tensile bond strength was determined through a cross-couplet test. Among the cement sand mortar used in this study, cement sand mortar of ratio 1:4 and thickness 15mm showed the maximum shear strength of 0.13MPa with the failure of blocks as the predominant failure while the PMM had shear bond strength of 0.12MPa with the failure of blocks as the predominant failure type. However, in case of the tensile bond strength testing, PMM showed the tensile bond strength of 0.19MPa, which was highest among all the test specimens used in this study. Considering both the tensile and shear bond strengths of the AAC masonry and based on the observed failure pattern, among all the combinations used in the experiment, either PMM or cement-sand mortar of ratio 1:4 and thickness of 15mm can be chosen for the AAC masonry.